Factors affecting satisfaction on antenatal care services in Sarawak, Malaysia: evidence from a cross sectional study - Rahman, M.M.; Ngadan, Deburra Peak; Arif, M.T. (Springer, 2016)
Background: High levels of satisfaction among women with the antenatal care services will increase the compliance of antenatal visits during pregnancy. Thus, this study was done to assess the level of satisfaction among women on the quality of antenatal care received and the factors influencing thereof. Methods: This was a cross-sectional study conducted in the three zones of Sarawak. Women aged 18 years and above, irrespective of ethnic groups, having children aged 3 years and below were included in the study. Data was collected by face-to-face interview using interview schedule. A validated Patient Satisfaction Questionnaire (PSQ-18) was used to assess the satisfaction with antenatal care. A total of 1236 data was analysed using IBM SPSS version 22.0. A p value <0.05 was considered as statistically significant. Results: A multinomial logistic regression analysis revealed that Bidayuh 17.4 % was less likely to be highly satisfied with antenatal care. Similarly, respondents with secondary level of education 29.9 % were less likely to be highly satisfied, whereas, respondents having primary level of education, 1.6 % were less likely to be highly satisfied. However, those who did not spend any money as out of pocket expenses were 1.935 times more likely to be highly satisfied with antenatal care. Conclusion: Overall the studied women were satisfied with the antenatal care services. Ethnicity, level of education and out of pocket expenses appeared to be important predictors of satisfaction with antenatal care. The finding recommends the community-based and language-specific interventions should be implemented to sustain the satisfaction of maternal care.